The impact of memorable eco-tourism experience on behavioral intention among tourists who took train trips to dabong, kelantan - Nur Afiqah Azman; Nur Afiqah Mohd Salleh; Nur Afni Fitriani Sufian; Nur Aiman Haina Hamidon (2022)
Ecotourism has seen as sustainable tourism since it is thought to conserve the ecology of a tourist location while also meeting the diverse demands of tourist. However, the most of recently develop ecotourism destinations have suffered from environment damage, restricted experiences, and decreased tourist arrivals. Therefore, the current study focuses on the connection between memorable tourism experiences and tourist satisfaction. A quantitative research study will be conducted online with 384 respondents who had visited Dabong, Kelantan, Malaysia. This paper intended to provide tour operators and tourism marketers with valuable insight into how to create and market a memorable tourism experience to tourists. Keywords: Ecotourism, memorable tourism experiences, behavioural intention, tourist satisfaction